Moderating Role of Political Connection Between Audit Evidence and Audit Quality - Oktri Supyati Jaisyul Usrah; Nurkholifah Burhanuddin; Grace T. Pontoh; Mediaty Mediaty (JAFFA, 2022)
This study aims to provide empirical evidence of the influence of the role of political connections as a moderator between audit evidence and audit quality at the Makassar Public Accountant Office. This study uses a quantitative approach and data collection using a questionnaire through a google form at Public Accountant Office in Makassar. The results showed that audit evidence had a significant positive effect on audit quality. The results of this study also show that the moderating variable of political connections cannot significantly weaken the effect of audit evidence on audit quality. This study provides evidence that public accountants at the Public Accountant Office in Makassar feel that audit evidence is an essential factor in the excellent quality of an audit assignment. Implementing a two-tier system can also reduce the degradative effect of political connections on audit quality and reduce agency conflicts in companies.